Optimized Rostering of Workforce Subject to Cyclic Requirements - Ramond, F.; De Almeida, D.; Dauzére-Pérés, S.; Sherali, H.D. (Informatica)
Optimized Rostering of Workforce Subject to Cyclic Requirements